IIUM students' perception on the implementation of library total quality management (TQM) - Ali, Abdiaziz Ahmed (Institute of Education, International Islamic University Malaysia, 2010)
This study attempts to examine the extent of total quality management (TQM) in IIUM library services. The main objective of this research is to investigate students' perception on TQM implementation in IIUM library. The significance of this study is to provide a clear understanding and implementation of TQM values in higher education in general and to determine students' perception on TQM principles practice in IIUM library in particular. For these objectives, a questionnaire was specially designed in order to get information from the respondents who were 370 IIUM students. To explain respondents' perception of implementation TQM in IIUM library services, descriptive statistics was employed in this study. A questionnaire of Five Points Likert Scale was used as an instrument to collect data of the study. In addition to that, frequencies, percentages, means, and standard deviations for each item of the survey questionnaire were also computed. Research analysis revealed that IIUM library tries to provide adequate quality services to satisfy students' needs. Thus, the findings of this study appear to be positive although it has been emphasized to improve quality services in IIUM library in order to be in line with the TQM requirements. However, the research has found that most of the students are contented with overall facilities provided by the management of IIUM library. Finally, this thesis discussed implications in terms of theoretical, practical and managerial implication. Also recommendations and suggestions were presented for future improvement.